GLOBAL TRENDS AND THEMATIC DYNAMICS IN GREEN ACCOUNTING RESEARCH (2000–2024): A BIBLIOMETRIC ANALYSIS OF SCOPUS PUBLICATIONS - Rahman, Anisa; Rohman, Abdul (Universitas Riau, 2025)
This study analyzed 925 Scopus-indexed documents from 2000–2024 using RStudio Bibliometrix to map trends, collaborations, and the evolution of green accounting research themes. Results show an 11.59% annual growth in publications, with Schaltegger and Gray as lead authors, and a shift in key topics from carbon accounting to biodiversity and accountability. Findings highlight a collaboration gap between developed and developing countries, and the dominance of institutions from the Global North, while engagement in developing countries remains low. This research contributes to scholarship by mapping international collaborations, understanding critical themes, and providing a roadmap for globally inclusive research. Practical implications include recommendations for cross-border collaboration and the development of integrated carbon reporting standards to drive business transitions toward sustainability. This study is limited by its data collection solely from English-language Scopus documents and its quantitative bibliometric approach. Consequently, qualitative aspects and other sources of basic data remain unexplored. Future research is recommended to incorporate content analysis and expand the data coverage for more comprehensive results.